2016
DOI: 10.1017/jns.2016.11
|View full text |Cite
|
Sign up to set email alerts
|

Impact of polyphenol-rich sources on acute postprandial glycaemia: a systematic review

Abstract: Increasingly, evidence suggests a role for polyphenols in blood glucose control. The objective of this systematic review was to evaluate the effect of polyphenol-rich sources in combination with carbohydrate sources on resulting postprandial glycaemic and insulin responses. A literature search was conducted using Medline, CINHAL and Web of Science databases. Selected studies included randomised controlled trials in which the association of polyphenol-containing food or beverage consumption with a carbohydrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 63 publications
0
50
1
Order By: Relevance
“…Since many FVB are rich in soluble fibers and polyphenols, the glycemic response for breads containing FVB may be expected to improve (the mechanistic effects of soluble fibers and polyphenols on the glycemic response of foods was briefly described in section 1). In particular, Coe and Ryan (2016) reported epidemiological data indicating that polyphenols reduce the peak and early-phase glycemic response and maintain the glycemic response in the later stages of digestion, suggesting that polyphenols in foods may have a beneficial effect on reducing the risk for type 2 13 diabetes. However, this effect has not been studied in depth in breads enriched with the most common FVB.…”
Section: Nutritional Improvement Of Bread Through the Utilization Of Fvbmentioning
confidence: 99%
See 1 more Smart Citation
“…Since many FVB are rich in soluble fibers and polyphenols, the glycemic response for breads containing FVB may be expected to improve (the mechanistic effects of soluble fibers and polyphenols on the glycemic response of foods was briefly described in section 1). In particular, Coe and Ryan (2016) reported epidemiological data indicating that polyphenols reduce the peak and early-phase glycemic response and maintain the glycemic response in the later stages of digestion, suggesting that polyphenols in foods may have a beneficial effect on reducing the risk for type 2 13 diabetes. However, this effect has not been studied in depth in breads enriched with the most common FVB.…”
Section: Nutritional Improvement Of Bread Through the Utilization Of Fvbmentioning
confidence: 99%
“…The effect of water-soluble fibers on the reduction of the glycemic response of products rich in starch has been demonstrated (Scazzina et al, 2013). In other cases, the presence of phenolic compounds, with potential for the inhibition of digestive enzymes (Coe and Ryan, 2016) or glucose trans-epithelial transporters (Moser et al 2016), may also be responsible for this nutritional improvement.…”
Section: Nutritional Improvement Of Cakes Through the Utilization Of Fvbmentioning
confidence: 99%
“…5 Plant-derived phenolic compounds have been shown to modulate blood glucose regulation through inhibition of α-glucosidase, α-amylase as well as the intestinal transporters, Na-dependent glucose co-transporter-1 (SGLT1) and facilitated Na-independent glucose transporter-2 (GLUT2). 6 Although appetite regulation is governed by complex signaling in the peripheral and central systems, its association with glucose metabolism adds complexity to energy intake and expenditure. It has been shown that consumption of low glycaemic index foods could influence shortterm control of appetite and satiety.…”
Section: Introductionmentioning
confidence: 99%
“…44 Fruit extracts, rich in polyphenols did not succeed in lowering glycaemic response to white bread except for baobab fruit extract which exerted benefits in postprandial insulin economy. 41 Fruit ingredients incorporation into bread constitute a novel approach which apart from lowering glycaemic and insulinaemic response, can also increase both the dietary fibre and phenolic acid content, improving its nutritional quality.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Baobab fruit and green tea extract were baked into white bread in the study by Coe et al 41 aiming to enhance its nutritional quality. There is evidence that the effect of polyphenol-rich fruits is more evident on insulin than glucose postprandial response.…”
Section: Breads Enriched With Fruit-based Ingredientsmentioning
confidence: 99%